2013
DOI: 10.1136/medethics-2013-101572
|View full text |Cite
|
Sign up to set email alerts
|

Consensus standards for introductory e-learning courses in human participants research ethics

Abstract: This paper reports the results of a workshop held in January 2013 to begin the process of establishing standards for e-learning programmes in the ethics of research involving human participants that could serve as the basis of their evaluation by individuals and groups who want to use, recommend or accredit such programmes. The standards that were drafted at the workshop cover the following topics: designer/provider qualifications, learning goals, learning objectives, content, methods, assessment of participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…Our program combines the availability of video lectures and other learning material with web-based interaction between students and tutors. Previous studies have found that on-line and on-site training result in rather similar improvements in the knowledge of research ethics [9,18]. Because web-based education, especially the Moodle environment, offers several advantages over on-site teaching for professionals, it may represent a very feasible method for education in research ethics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our program combines the availability of video lectures and other learning material with web-based interaction between students and tutors. Previous studies have found that on-line and on-site training result in rather similar improvements in the knowledge of research ethics [9,18]. Because web-based education, especially the Moodle environment, offers several advantages over on-site teaching for professionals, it may represent a very feasible method for education in research ethics.…”
Section: Discussionmentioning
confidence: 99%
“…The opportunity to share experiences with different research related issues might increase the appreciation of the multidimensional nature of bioethics [9]. The inclusion of a discussion portal into our course program will be considered in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both might benefit from training that highlights engagement as a legitimate focus of ethics review [35]. This might complement existing research ethics modules [36][37][38][39][40][41] developed by several institutions [42][43][44][45][46][47][48] that highlight practical skills using interactive features [36,39,41,[49][50][51][52][53][54][55][56]. This might also complement existing modules featuring engagement as a key part of ethical research (FHI 360) [46]; of ethical HIV vaccine trials, of ethical adolescent trials, and of public health research (TRREE) [42].…”
Section: Discussionmentioning
confidence: 99%